Economic security of life support of citizens on the basis of an innovative corporate management system of housing and communal services - V. M. Yakovlev; S. F. Vashchenko (Путеводитель предпринимателя, 2020)
In the article questions of formation of an innovative life support system of citizens of the Russian Federation on the basis of construction of corporate model of management of housing and communal services of municipalities are considered. The detailed analysis is carried out, shortcomings of the existing system of mainly administrative management of comparison to opportunities of new system of economic management of housing and communal services come to light. Importance of observance of parameters of economic security of a life support system of citizens of Russia is emphasized.